Message from the Editor in Chief - Riza Muhida (University of Bandar Lampung (UBL), 2013)
Welcome to the Third Issue of International Journal of Engineering Science and Technology Development (IJEST) on December 2013. In this issue of IJEST, we present to our readers selected articles related to Engineering, Science and Computer and Tehnology. Five papers are presented from Indonesia, Malaysia and Saudi Arabia.The first article by Abdul Aziz Ahmad and Assoc. Prof. Dr. Raihan Othman from International Islamic University Malaysia (IIUM), Malaysia with the title: Recent Advances in Biofuel Cell and Emerging Hybrid System. The second article by Prof. Dr. Priyo Suprobo,Faimun and Arie Febry from Institute Technology Surabaya (ITS), Indonesia with the title: Infrastructure Health Monitoring System (SHM) Development, a Necessity for Maintenance and Investigation . The third article by Dr. Riza Ainul Hakim, from King Abdulaziz University , Saudi Arabia, with the title: Seismic Assessment of RC Building Using Pushover Analysis The fourth article by Ida Bagus Ilham Maliki from Universitas Bandar Lampung, Indonesia with the title: Public Transport Crisis in Bandar Lampung. The fifth article by Marzuki, Maria Shusanti F and Andala Rama Putra from Bandar Lampung University, Indonesia with the title: The E-Internal Audit ISO 9001:2008 Based on Accreditation Form Assessment Matrix in Study Program for Effectiveness of Monitoring Accreditation With these selections I sincerely hope that everyone has something to gain from this issue and thank you to article contributors and reviewers for making this issue possible. To all prospective author, we are welcome and please sent your article to the editors.